Analysis of Marketing Margin Behaviour Using Econometric Model: The Case of Groundnut in East Java - Hadi, Prajogo Utomo (Jurnal Agro Ekonomi, 1990)
IndonesianPedagang sering dikritik sebagai pihak yang membuat harga komoditas pertanian di tingkat petani tetap rendah dan harga di tingkat konsumen tinggi serta cenderung memperbesar marjin pemasaran. Studi ini bertujuan menganalisis perilaku marjin pemasaran kacang tanah di Jawa Timur dan secara spesifik menguji hipotesa bahwa pedagang tidak mempraktekkan strategi price levelling dan bersikap netral terhadap risiko harga. Dengan menggunakan metoda ekonometrik, hasil analisis menunjukkan bahwa pedagang menerapkan strategi tersebut di atas dan bersikap netral terhadap risiko harga, dan marjin pemasaran tidak meningkat dalam jangka panjang. Berdasarkan hasil penelitian ini, kebijaksanaan stabilisasi harga kacang tanah tidak dianjurkan.EnglishMiddlemen are often blamed as those practicing a behaviour which keeps price of agricultural commodities low at the farmgate and high at the consumer level and tend to widen the gap between these two price levels, i.e., the marketing margins. The present study aims to analyze the behaviour of marketing margins of groundnut in East Java. It specifically tests the hypotheses of the non-existence of price levelling behaviour and price-risk neutrality of the middlemen. Employing an econometric method, the present study found that middlemen practiced price levelling behaviour and did not respond to price risk and the marketing margins has not increased in the long-run. On the basis of these results, policies stabilising the price of groundnut are not suggested.